AN ANALYSIS OF TENTH GRADE STUDENTS’ DIFFICULTIES IN COMPREHENDING RECOUNT TEXT - Eko Prayitno; Dewi Sartika; Rekha Asmara (STKIP Persada Khatulistiwa Sintang, 2021)
This study aimed to recognize the problems faced by the tenth graders of SMA Negeri 1 Jejawi and to determine the factors that influenced students’ difficulties in comprehending recount text. This study was a qualitative research. The subject of the study was the tenth grade students of SMA Negeri 1 Jejawi in academic year of 2019/2020. The techniques of collecting the data were interview and reading comprehension test. To analyses the data, reducing, data displayed, content analysis, and draw conclusion were applied. The result of the study showed that there were 68.7% students had difficulties in finding the main idea, 70.15% students had difficulties in understanding vocabulary, 66% students had difficulties in finding reference, 59.3% students had difficulties in finding purpose of the text, 67.24% students had difficulties in finding detail information, and 81.95% students had difficulties in determining the generic structure of the text. Some factors influenced students’ difficulties in comprehending recount text were material that has long passage, limitation of words, learners’ background, and environment.